Análisis preliminar de un cuestionario de evaluación de la percepción social de la contaminación atmosférica (2015)
ABSTRACT: Objective To analyze the psychometric properties and the structural organization of a questionnaire designed to assess the social perception of air pollution and its health risks in the Valle de Aburrá (Colombia), a geographical area where environmental problems associated with air pollution have been identified. Methods A descriptive study was carried out, in which a questionnaire was designed and validated to determine three dimensions of social perception of air pollution: the socio-territorial dimension, the socio-cognitive dimension and the behavioral dimension. Some socio-demographical variables were also included. After the pilot study, the dimensions of the analysis were organized into 12 categories, made up of 111 items with Likert scales of four or five response options. The instrument was applied to a non-random sample of 318 participants, who were residents of Medellin city and Girardota town. Results After exploratory factor analysis (varimax rotation), the questionnaire was reduced to 68 items assessing seven dimensions of social perception of air pollution and its health risks. The total variance explained is 75 %, and the overall Cronbach's alpha reliability was 0.9. Discussion The dimensions found allow us to develop an approach to the structural organization of the social perception of air pollution in the context of study. Although some socio-cognitive and behavioral dimensions were confirmed, the socio-territorial dimension and the personal involvement variable were not configured as structural components and, conceptually, they need to be reworked. Confirmatory structural analysis of the dimensions of the questionnaire is required.